New Zealand : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses prospects for potential growth, house prices, household debt, and financial stability risks, and tax policy reforms in New Zealand. Despite having world-class institutions and strong policy framework, income levels remain low relative to other Organisation for Economic Co-operation and Development (OECD) countries. During 1980-2014, per capita income levels have remained about 20 percent below the OECD's average income. Longstanding structural issues need to be addressed to boost potential growth. House prices and household debt have increased rapidly in New Zealand over the past two decades. New Zealand's low national saving rate is a source of vulnerability and likely contributes to the relatively high interest rates needed to attract foreign capital.